2021
DOI: 10.1021/acs.cgd.0c01198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionothermal Conditions on the Crystallization of Organically Templated Uranyl Sulfate Compounds

Abstract: Seven novel uranyl sulfate compounds were crystallized by ionothermal synthesis methods through systematic changes in experimental conditions. The parameters explored were temperature, soak time, cooling rate, and reactants, including uranium­(VI) salt, a uranium­(VI) concentration in the ionic liquid, and the pH by cosolvent addition. The ionic liquid 1-ethyl-3-methylimidazolium ethyl sulfate (EMIm-EtSO4) was used in each experiment. Although the seven uranyl sulfate compounds all contained the EMIm organic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The symmetric stretch of the uranyl ion in the compounds studied here (895–907 cm –1 ) is in accord with uranyl sulfates . The spectrum of TSUBOB-1 contains symmetric and antisymmetric stretching bands of (SO 4 ) at 991, 1002, 1067, 1153, and 1179 cm –1 , as well as in the spectrum of TSUDS at 949, 976, 1053, and 1108 cm –1 …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The symmetric stretch of the uranyl ion in the compounds studied here (895–907 cm –1 ) is in accord with uranyl sulfates . The spectrum of TSUBOB-1 contains symmetric and antisymmetric stretching bands of (SO 4 ) at 991, 1002, 1067, 1153, and 1179 cm –1 , as well as in the spectrum of TSUDS at 949, 976, 1053, and 1108 cm –1 …”
Section: Resultssupporting
confidence: 61%
“…25 The spectrum of TSUBOB-1 contains symmetric and antisymmetric stretching bands of (SO 4 ) at 991, 1002, 1067, 1153, and 1179 cm −1 , as well as in the spectrum of TSUDS at 949, 976, 1053, and 1108 cm −1 . 26 Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS). The DRIFTS spectra of TSUBOS-1, TSUBOB-1, and TSUDS are shown in Figures S5−S7.…”
Section: Inorganicmentioning
confidence: 99%
“…This heat treatment with a lower soak temperature and faster cooling rate produces kinetically favored products. [42] Because the uranyl dibutyl phosphate compounds form with both heat treatments while the uranyl diethyl phosphate compound does not, it is possible that the butyl groups provide greater stabilization of the crystal structure (i. e. a more thermodynamically favored product) than the ethyl counterparts. In changing the organic functional group to methyls, the uranyl ion adopts a different coordination, topology, and thus crystal packing in compound 1, which likely allows the even shorter methyl groups to provide enough van der Waals interactions to stabilize the overall crystal structure.…”
Section: Heat Treatment Conditions and Resultant Productsmentioning
confidence: 99%
“…Overall, 30 reactions incorporated changes in co‐solvents with variable pH, heat treatments, and ionic liquid phosphate anion with variable lengths of the organic functional groups. We previously showed that co‐solvents can affect topologies of uranyl sulfate structural units in conjunction with different heat treatments that promote crystal growth of kinetically or thermodynamically favored products [42] . The main focus here was to apply optimal parameters from the previous study to synthesize uranyl phosphate compounds to investigate the role of the ionic liquid anion in crystal structure stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation